Towards practical quantum metrology - Nichols, Rosanna (2019)
This thesis aims to help in bridging the gap between the ideals of theoretical quantum metrology and its practical application. We take three major approaches to achieving this aim: to investigate the effect of noise on metrological schemes, to study the role of resources and to devise ways to engineer effective probe states from experimentally feasible elements. We find that noise is detrimental to measurement precision but that this may be overcome by thinking outside of the asymptotic regime. Considering resources, whilst entanglement may provide an advantage, it is only useful in limited circumstances and even in this case a very small entangled state may perform as well as a large one. This is also true in multiparameter metrology, where we find that it is possible for the simultaneous estimation of phase and noise to be advantageous, even when the parameters are not fully compatible. We discuss strategies for multiparameter estimation in both discrete and continuous variable formalisms. In the continuous variable formalism, we go beyond the consideration of entanglement as a resource and construct a generalised resource theory for Gaussian states and operations which has particular cases in entanglement, steerability and squeezing. We provide a measure for this resource as well as a no-go theorem for its distillation. Finally, we use a genetic algorithm to devise state engineering schemes to produce highly sensitive states for quantum metrology.